Metal exposure in the Greenlandic ACCEPT cohort: follow-up and comparison with other Arctic populations - Maria Wielsøe; Manhai Long; Jens Søndergaard; Eva Cecilie Bonefeld-Jørgensen (International Journal of Circumpolar Health)
Humans are exposed to metals through diet and lifestyle e.g. smoking. Some metals are essential for physiologically body functions, while others are non-essential and can be toxic to humans. This study follows up on metal concentrations in the Greenlandic ACCEPT birth-cohort (mothers and fathers) and compares with other Arctic populations. The data from 2019 to 2020 include blood metal concentrations, lifestyle and food frequency questionnaires from 101 mothers and 76 fathers, 24–55 years, living in Nuuk, Sisimiut, and Ilulissat. A high percentage (25–45%) exceeded international guidance values for Hg. For the mothers, the metal concentrations changed significantly from inclusion at pregnancy to this follow-up 3–5 years after birth; some increased and others decreased. Most metals differed significantly between mothers and fathers, while few also differed between residential towns. Several metals correlated significantly with marine food intake and socio-economic factors, but the direction of the correlations varied. Traditional marine food intake was associated positively with Se, As and Hg. To the best of our knowledge, this study provides the most recent data on metal exposure of both men and women in Greenland, elucidating metal exposure sources among Arctic populations, and documents the need for continuing biomonitoring to follow the exceeding of guidance values for Hg. [Figure: see text]